A characterisation of tool-ply friction behaviors in thermoplastic composite. (2017) - Lee, Jeong-Min; Kim, Byung-Min; Lee, Chan-Joo; Ko, Dae-Cheol
Abstract: Generally, the compression forming process is mainly used to fabricate the pre-form of CFRP product in resin transfer molding(RTM) process. The laminate is deformed under the low pressure because only fabrics and binders are used in pre-form process. However, the laminate consisted of prepreg is deformed under the high pressure and warm temperature to improve the surface quality and remove the voids in perperg compression forming(PCF) process. Therefore, the evaluations of tool-ply friction behaviors are required under the condition of high pressure and warm temperature. Several parameters have been investigated to determine their effect on the friction coefficient between the tool and laminate: normal pressure, laminate temperature, tool temperature, atmosphere temperature, and laminate orientation. In this study, the friction behaviors were evaluated for several important parameters of normal pressure, laminate orientation and atmosphere temperature. This paper describes two experimental method for measuring the friction behaviors of thermoplastic composites. The pull-through and rotational friction tests were performed to compare the friction behaviors according to the operating direction in the tests. In addition, the relationship of stribeck curve was evaluated under the conditions of high pressure and warm temperature.